The Mechanics of the Industrial Revolution - Kelly, Morgan; Mokyr, Joel; Ó Gráda, Cormac (Journal of Political Economy, 2023)
Although there are many competing explanations for the Industrial Revolution, there has been no effort to evaluate them econometrically. This paper analyzes how the very different patterns of growth across the counties of England between the 1760s and 1830s can be explained by a wide range of potential variables. We find that industrialization occurred in areas that began with low wages but high mechanical skills, whereas other variables, such as literacy, banks, and proximity to coal, have little explanatory power. Against the view that living standards were stagnant during the Industrial Revolution, we find that real wages rose sharply in the industrializing north and declined in the previously prosperous south.